Felix Frankfurter papers - Frankfurter, Felix, 1882-1965.; Buxton, Frank W. (Frank William), 1877-1974.; Moody, William H. (William Henry), 1853-1917.
Correspondence, memoranda, diaries, oral history interviews, writings, speeches, notes, legal file, newspaper clippings, printed material, photographs, and other papers reflecting Frankfurter's involvement with significant political and social movements and events and his acquaintance with leaders in many segments of society. Documents his early years as a lawyer in public service, his tenure at Harvard Law School (1914-1939), and his years as associate justice of the U.S. Supreme Court (1939-1962). Also includes material pertaining to Frankfurter's participation in the Paris Peace Conference (1919-1920) as a member of the Zionist Commission, his years as trustee of and contributor to The New Republic, and his role in the New Deal as unofficial advisor to Franklin D. Roosevelt.
Subjects include the judicial process, law, development of legal and social institutions, the personalities and legal philosophies of members of the Supreme Court, the Sacco-Vanzetti case, and the relation between law and social action. Other topics include banking structure, a survey of crime and criminal justice in Boston conducted by Harvard Law School, foreign affairs, independent regulatory commissions, industrial relations, labor injunctions, literary events and personages between the two world wars, the National Industrial Recovery Act of 1933, national politics in the United States and Great Britain, public utilities, railroad reorganization, and unemployment. Also includes material pertaining to various organizations including the American Civil Liberties Union, American Law Institute, Cleveland Foundation, National Commission on Law Observance and Enforcement (U.S. Wickersham Commission), National Consumers' League, Social Science Research Council, and U.S. War Labor Policies Board.
Includes some papers (1906-1910) of William Henry Moody and files containing materials by or about Oliver Wendell Holmes including correspondence (1929-1935) of his law clerks. Also includes Frank W. Buxton's memoir, Chum Felix Frankfurter : A Retired Journalist's Account of a Genius In His Off-duty Hours (197-).
Family correspondents include Frankfurter's wife, Marion Denman Frankfurter, and his sisters, Estelle S. Frankfurter and Ella Rogers. Other correspondents include Dean Acheson, Louis Dembitz Brandeis, Emory R. Buckner, Charles C. Burlingham, Frank W. Buxton, Loring Christie, Alfred E. Cohn, Herbert David Croly, Albert Einstein, Herbert Feis, Jerome Frank, Albert M. Friedenberg, Henry J. Friendly, Francis Hackett, Learned Hand, Julian Huxley, Harold Joseph Laski, W.S. Lewis, Max Lowenthal, Archibald MacLeish, Reinhold Niebuhr, Eleanor Roosevelt, Franklin D. Roosevelt, and Henry Lewis Stimson.
Microfilm edition available
Letter from Archibald MacLeish to Felix Frankfurter, May 15, 1939, also available through the Library of Congress Web site.
Microfilm produced from originals in the Manuscript Division.
Professor of law and associate justice of the U.S. Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Buckner, Emory R. -- 1877-1941 -- Correspondence; Burlingham, Charles C. -- 1858-1959 -- Correspondence; Buxton, Frank W. -- 1877-1974 -- Correspondence; Christie, Loring -- Correspondence; Cohn, Alfred E. -- 1879-1957 -- Correspondence; Croly, Herbert David, -- 1869-1930 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Feis, Herbert, -- 1893-1972 -- Correspondence; Frank, Jerome, -- 1889-1957 -- Correspondence; Frankfurter, Estelle S. -- Correspondence; Frankfurter, Marion Denman, -- 1890-1975 -- Correspondence; Friedenberg, Albert M. -- 1881-1942 -- Correspondence; Friendly, Henry J. -- Correspondence; Hackett, Francis, -- 1883-1962 -- Correspondence; Hand, Learned, -- 1872-1961 -- Correspondence; Holmes, Oliver Wendell, -- 1841-1935.; Huxley, Julian, -- 1887-1975 -- Correspondence; Laski, Harold Joseph, -- 1893-1950 -- Correspondence; Lewis, W. S. -- 1895-1979 -- Correspondence; Lowenthal, Max -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Niebuhr, Reinhold, -- 1892-1971 -- Correspondence; Rogers, Ella -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; United States. -- Supreme Court; United States. -- War Labor Policies Board; United States. -- Wickersham Commission; United States; American Civil Liberties Union; American Law Institute; Cleveland Foundation; Harvard Law School; National Consumers' League; Social Science Research Council (U.S.); Zionist Commission; New republic; Associations, institutions, etc; Banks and banking -- United States; Constitutional law -- United States; Crime -- Massachusetts -- Boston; Criminal justice, Administration of -- Massachusetts -- Boston; Endowments -- Ohio -- Cleveland; Independent regulatory commissions -- United States; Industrial relations -- United States; Judicial process; Labor disputes -- United States; Law; Law -- Philosophy; Law -- United States; Literature; New Deal, 1933-1939.; Public utilities -- United States; Railroads -- United States; Sacco-Vanzetti Trial, Dedham, Mass., 1921.; Social action -- United States